MGMT promoter methylation status and prognosis of patients with primary or recurrent glioblastoma treated with carmustine wafers. (December 2013) - Gutenberg, A.; Bock, H. C.; Brück, W.; Doerner, L.; Mehdorn, H. M.; Roggendorf, W.; Westphal, M.; Felsberg, J.; Reifenberger, G.; Giese, A.
Abstract The prognostic role of O6-methylguanine-DNA methyltransferase (MGMT) promoter methylation in glioblastoma patients treated with carmustine (BCNU) wafer implantation is unclear. Here, we report on a retrospective study of 47 patients with either newly diagnosed (30 patients) or recurrent (17 patients) glioblastoma (WHO grade IV) treated with BCNU (bis-chloroethylnitrosourea) wafers. Thirteen of the newly diagnosed patients received local BCNU and irradiation only (first-line BCNU), while 17 patients additionally received concomitant and adjuvant temozolomide (TMZ) radiochemotherapy (first-line BCNU + TMZ). Of the 17 patients treated for recurrent glioblastoma (second-line BCNU), 16 had received radiotherapy with concomitant and adjuvant TMZ as an initial treatment. Median overall survival (OS) did not significantly differ between 19 patients with MGMT promoter methylated tumors when compared to 28 patients with unmethylated tumors (18.9 vs 15.0 months; p = 0.1054). In the first-line BCNU + TMZ group, MGMT promoter methylation was associated with longer OS (21.0 vs 11.1 months, p = 0.0127), while no significant survival differences were detected in the other two subgroups. Progression-free survival did not significantly differ between patients with and without MGMT promoter methylated tumors in the entire patient cohort or any of the three subgroups. The first-line BCNU + TMZ group showed no significant difference in OS when compared to the first-line BCNU group (18.9 vs 14.7 months), but tended to have more therapy-related adverse effects (53% vs 24%, p = 0.105). In summary, MGMT promoter methylation showed a non-significant trend toward longer survival in our patient cohort. The combination of TMZ radiochemotherapy with local delivery of BCNU did not provide a significant survival benefit compared to local BCNU alone, but was associated with a higher rate of adverse effects. Owing to the small number of patients investigated, however, these findings would need to be corroborated in larger patient cohorts.